2000
DOI: 10.1021/ma991491e
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Micelles of Polyisobutylene-block-poly(methacrylic acid) in Aqueous Medium

Abstract: Four amphiphilic block copolymers polyisobutylene-block-poly(methacrylic acid) (IB m -MAA n ; m = 70−134, n = 52−228) were synthesized and transferred into aqueous medium at pH 10−12. Their structure in solution was characterized by fluorescence correlation spectroscopy (FCS), static and dynamic light scattering (SLS, DLS), analytical ultracentrifuge (AUC), and by transmission electron microscopy (TEM) with freeze-fracturing and staining techniques. DLS data, AUC sedimentation traces, and TEM images indicate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 11 publications
(15 reference statements)
11
115
0
1
Order By: Relevance
“…25,26 A vesicle structure is not possible either, because the particle size and the aggregation number (which will be discussed later) are far too low compared to the reported values for vesicle. 10,27 A ρ of approximately 0.9 characterizing a core-shell structured micelle for polyisobutylene-b-poly(methacrylic acid) block copolymers has been reported by Schuch et al 10 Therefore it is believed the ρ = 0.88 for the P(MAA-b-MMA) polymer also corresponds to a micellar structure with a dense MMA core and MAA shell, which is consistent with the result obtained from potentiometric titration. Moreover, comparison of the measured radii of the micelle (~23nm before neutralization, and ~ 38nm after neutralization) with the contour length of a single polymer chain (~ 40nm) also indicates that a singlelayered micellar structure is the most probable microstructure.…”
Section: Static Light Scatteringsupporting
confidence: 86%
See 1 more Smart Citation
“…25,26 A vesicle structure is not possible either, because the particle size and the aggregation number (which will be discussed later) are far too low compared to the reported values for vesicle. 10,27 A ρ of approximately 0.9 characterizing a core-shell structured micelle for polyisobutylene-b-poly(methacrylic acid) block copolymers has been reported by Schuch et al 10 Therefore it is believed the ρ = 0.88 for the P(MAA-b-MMA) polymer also corresponds to a micellar structure with a dense MMA core and MAA shell, which is consistent with the result obtained from potentiometric titration. Moreover, comparison of the measured radii of the micelle (~23nm before neutralization, and ~ 38nm after neutralization) with the contour length of a single polymer chain (~ 40nm) also indicates that a singlelayered micellar structure is the most probable microstructure.…”
Section: Static Light Scatteringsupporting
confidence: 86%
“…8,9 Schuch et al proposed the formation of small vesicle-like structure from poly(isobutylene)-b-poly(methacrylic acid) in aqueous medium. 10 The formation of three-layer micelle from pH responsive tri-block ((polystyrene-b-poly(2-vinylpyridine)-bpoly(ethylene oxide)) copolymer in water was studied by Gohy et al 11 It has been demonstrated that the pH sensitive poly(2-vinyl pyridine) shell was used to tune the size of the vesicle. This effect was mainly attributed to electrostatic repulsion between the charged polyelectrolyte chains.…”
Section: Introductionmentioning
confidence: 99%
“…However, data by Schuch et al 44 for polyisobutylene-block-poly(methacrylic acid) in water confirm this scaling behavior for large degree of polymerization, while for small N A some systematic deviations from the above power law seem to occur. This study 44 (as well as ref 42) has the merit that data close to the cmc could be taken, and it was shown that the micelle formation near the cmc is spread out over about a full decade in concentration. Finally, we mention the work of Willner et al, 45 who studied the structure of micelles varying the length of the block in the corona over a wide range and showed that the starlike model is applicable only for N B .…”
Section: Concluding Remarks and Comparison With Experimentsmentioning
confidence: 88%
“…9,11,14,18,[23][24][25][26][27] In fact, this point has already been made by several authors, and systemspecific predictions 27 have been made for several blockcopolymer-solvent systems and also carried out a comparison with experiment. 37 Further experimental studies where these theoretical predictions are tested can be found in refs [38][39][40][41][42][43][44][45]. Such studies are also clearly difficult to perform, since the critical micelle concentration (φ cmc ) seems to decrease almost exponentially with N, at least according to the model calculations.…”
Section: Introductionmentioning
confidence: 99%
“…This could however, suggest that the structures observed after the critical temperature are resulting from the formation of a new type of micelle rather than a simple clustering of the individual micelles. Chang et al [34] reported large aggregates of micelles that retain a relatively narrow size distribution above the cloud point while Faust and Schuch [35] suggested the presence of regular superstructures, e.g. vesicles.…”
Section: Thermo-responsive Behaviormentioning
confidence: 99%